Health state utility estimation of Mycobacterium avium complex pulmonary disease using a time trade-off approach. (31st December 2023) - Murata, Tatsunori; Morimoto, Kozo; Matsuyama, Fujio; Yamada, Mayumi; Feliciano, Joseph; Hassan, Mariam
Abstract: Aims: To obtain appropriate health state utility values for cost-effectiveness analyses of new Mycobacterium avium complex pulmonary disease (MAC-PD) treatments. The impact of MAC-PD severity and symptoms on quality of life (QoL) also were quantified. Methods: A questionnaire describing four health states, MAC-positive severe, MAC-positive moderate, MAC-positive mild, and MAC-negative, was developed based on St. George's Respiratory Questionnaire (SGRQ) Symptom and Activity scores from the CONVERT trial. The time trade-off (TTO) method with ping-pong titration procedure was used to estimate health state utilities. Regression analyses assessed the impacts of covariates. Results: Of 319 Japanese adults (49.8% female, mean age 44.8 years), mean (95% CI) health state utility scores (MAC-positive severe, MAC-positive moderate, MAC-positive mild, and MAC-negative) were 0.252 (0.194–0.310), 0.535 (0.488–0.582), 0.816 (0.793–0.839), and 0.881 (0.866–0.896), respectively. MAC-negative state utility scores were significantly higher than MAC-positive severe (mean difference [95% CI], 0.629 [0.574–0.684]), MAC-positive moderate (0.346 [0.304–0.389]), and MAC-positive mild (0.065 [0.048–0.082]) scores ( p < .001 each). Most participants would trade survival duration to avoid MAC-positive states (97.5% to avoid MAC-positive severe; 88.7% MAC-positive moderate; 61.4% MAC-positive mild). Regression analyses to investigate the impact of background characteristics showed similar utility differences between health states when not adjusted for covariates. Limitations: Some participant demographics differed from the general population; however, this did not impact utility differences among health states as regression analyses adjusting for demographics did not affect these differences. Similar investigations are needed among patients with MAC-PD and in other countries. Conclusions: This study evaluating the impact of MAC-PD on utilities using the TTO method demonstrates that differences in utilities are dependent on the severity of respiratory symptoms and their impacts on daily activities and QoL. These results could contribute to a better quantification of the value of MAC-PD treatments and improve assessments of cost-effectiveness.